Qualitative and quantitative determination of the mineralogical composition of archaeological pigments by X-ray diraction and modeling of the experimental intensities according to the Rietveld method - Asto, Esteban (2022)
The Pampa la Cruz archaeological site is located on a marine terrace, 200 meters from the coast of the Huanchaco district in the Trujillo city. Due to the importance of this archaeological complex, one of the great challenges is the study of its mural paintings and pigments for its preservation. Based on this perspective, the present investigation was developed with the purpose of studying and qualitatively and quantitatively determining the mineralogical composition of mural pigments by powder X-ray diraction and, in this way, determining the presence of degrading agents. The quantitative analysis was performed by the Rietveld method, in order to obtain information on the structural parameters and the weight percentage of each identied phase. The mineralogical  composition  of the pigments was determined, finding a high percentage of quartz, various clays as minor phases and halite salt; the latter in a small proportion and as an external contaminant. These results are expected to contribute to the preservation, restoration and maintenance of this archaeological site.